2021
DOI: 10.3390/su13063569
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation Response to Goats Grazing Intensity in Semiarid Hilly Grassland of the Loess Plateau, Lanzhou, China

Abstract: Quantitatively estimating the grazing intensity (GI) effects on vegetation in semiarid hilly grassland of the Loess Plateau can help to develop safe utilization levels for natural grasslands, which is a necessity of maintaining livestock production and sustainable development of grasslands. Normalized difference vegetation index (NDVI), field vegetation data, and 181 days (one goat per day) of GPS tracking were combined to quantify the spatial pattern of GI, and its effects on the vegetation community structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Diversity of Shannon index and richness index (Chao1, ACE) were calculated using "phyloseq" package [48]. Nonlinear regression and spearman correlation analyses were performed using the "survival" and "basicTrendline" packages, respectively [49]. Heatmaps were used to illustrate the Z-score-normalized relative abundance of N-cycling functional genes using the "pheatmap" package [50].…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Diversity of Shannon index and richness index (Chao1, ACE) were calculated using "phyloseq" package [48]. Nonlinear regression and spearman correlation analyses were performed using the "survival" and "basicTrendline" packages, respectively [49]. Heatmaps were used to illustrate the Z-score-normalized relative abundance of N-cycling functional genes using the "pheatmap" package [50].…”
Section: Statistical Analysesmentioning
confidence: 99%
“…In July 2022, during the field survey, sixty samples (Figure 1) were set up in areas with typical grazing path distribution based on the distribution characteristics of grazing behavior and other factors, including accessibility and terrain (Figure 1), which were evenly distributed on the hilltop (No. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], hillside (No. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40], and hillbottom (No.…”
Section: Sample Datamentioning
confidence: 99%
“…Grazing paths are diverse, with primarily parallel, oblique, and grid patterns [14]. In contrast, in areas with high slopes, animals move at a lower rate, so the density and tortuosity of grazing paths are greater [15]. Zhang [16] found that grazing has an influential effect on the structure of plant communities, with foraging and trampling by goats reducing plant density as well as cover.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the designed experiments, GD under real-world conditions have rarely been quantified because of the limitations of efficient monitor technology and available data. Some studies have focused on quantifying GD through vegetation indices and ground observation visually or by using time-lapse cameras [15][16][17], while some other researchers have attempted to quantify GD only by the remote sensing indices [1,17,18]. However, these studies usually provide rough estimates based on some specific indicators, which may not be sufficient for precise and reasonable management of grassland.…”
Section: Introductionmentioning
confidence: 99%